Perlindungan Korban Kekerasan Dalam Rumah Tangga Dalam Hukum Pidana Indonesia - La Jamaa (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: The protection of Domestic Violence Victims in the Indonesian Criminal Law. The existence of the Law No. 23 Year 2004 on the Elimination of Domestic Violence are expected to provide legal protection for victims of domestic violence (KDRT) significantly. The form of protection regulated in this Act is the temporary protection of the police, the courts and the protection of victims in the placement of